Perception of Importance of Physical Activity and Factors for Noncompliance to Physical Activity among Adult Type 2 Diabetic Patients - Taranum, Arshiya; Kalasker, Pavan (National Journal of Community Medicine, 2016)
Background: Diabetes is growing epidemic in India with more than 65 million diabetic individuals currently diagnosed with the disease. Regular physical activity is a cornerstone of type 2 diabetes management, but is often neglected and underutilized. Objectives: To determine the pattern and the factors for noncompliance to physical exercise recommendation among type 2 diabetic patients. Materials and Methods: It is a facility based cross-sectional study conducted on 125 type 2 diabetic patients who were interviewed using pretested, predesigned questionnaire on physical activity. Results: The reported levels of physical activity were low and only 9.6% of the studied population met the recommended guidelines, though 92% had perception about the importance of physical activity. Main factors for the non-compliance were Poor health condition or disease (45.7 %), lack of time (42.4%), feel tired after exercise (31.2%), inaffordability of suitable sportswear (30.4%). Conclusion: The majority of patients with type 2 diabetes does not engage in regular physical activity, with a rate significantly below recommended levels.